Audiovisual education of sexuality: a methodological proposal for image and sound analysis and study - Ricardo Desidério da Silva (Travessias, 2020)
Considering that images educate and are immersed in our daily lives, they still enable a variety of meanings. These meanings that submit us to a reflection of what would be its relationship with education. Is every video educational? How can we go beyond a simplistic look at what images and sounds represent? How to (re) mean your senses? These and many other possible questions lead us to think about its use in the school environment, since it may bring very relevant contributions to the teaching and learning process of the student, especially when linked to the theme of sexuality. In this sense, the text aims to present a methodology for the works that will be developed in Sexual Education projects at school from the analysis and study of images and sounds. It is a methodological alternative that is not limited in its use, and may be suitable for any other specific methods that you intend to use in your work and/or your research. It is also hoped that it will enable new approaches with the same purpose of analyzing images and sounds.